P63 Botulinum toxin a for post craniotomy head pain: a single centre case series of 11 patients. Issue 3 (14th February 2019) - Lavin, T
Abstract : Objectives: Botulinum Toxin for post craniotomy head pain is not an established therapy. One small case series commented that it was effective in 3 patients. 1 We report our single centre experience. Design: We performed a retrospective review of case notes of all patients treated with Botox for persistent post craniotomy or craniotomy head pain at Greater Manchester Neurosciences Centre, UK. All patients treated with Botulinum Toxin from 2014 at Greater Manchester Neurosciences Centre are listed on a central database, irrespective of indication. From the database 11 patients were identified who had received Botulinum Toxin A for post craniotomy scalp pain. Subjects: Eleven (n=11) patients were identified. The mean age was 43 year. Of the 11 patients; 6 were women and 5 were men. The majority of patients underwent surgery for medically intractable epilepsy (n=7). Methods: Information obtained: -Demographics -Date, indication and type of initial cranial neurosurgery Headache Characteristics (site, descriptors, duration, frequency) -Previous medical therapy -The presence of Epileptic Seizures -Frequency, dose and site of Botulinum Toxin injection -Response. Results: A majority of patients (10/11) reported improvement in headache burden with 6 patients reported being pain free with no further daily headache. The duration of this effect varied from 4 to 12 weeks. No specific headache characteristic (site, descriptor) predicted a favourable response. Of the remaining 5 who continue to report daily head pain, 4 felt the burden was more manageable. One patient felt there was no response. Of the 5 patients with persistent headaches, 3 were chronic epileptics with ongoing seizures, compared to only 1 patient in the responder group. Conclusions: This case series is limited by small numbers and no objective headaches made prior or post therapy. Botulinum Toxin A appears to have a beneficial effect in the management of chronic post craniotomy head pain within this small sample with complete abolition of pain in 55%. The presence of ongoing epileptic seizures may indicate a poor response. Further controlled studies are warranted.